(untitled) (مجلة إحالات, 2026)
This research aims to provide an analytical presentation on one of the most important modern books, which discussed in depth the issues of narrative and narrative, and concerned with the analysis of narrative discourse, in modern and innovative ways, and by that we mean the book: “Narrative and narrative and narrative - a presentation of the theories of contemporary Arab narrative, and analyzes of some of its texts -”, by the well-known critic Dr. Abd al-Malik Murtada; Where we meet in it a set of deep analyzes and distinguished scientific studies, in which the researcher discussed several issues that occupy a high position in the Arab narrative.